Molecular characterization of influenza A viruses circulating in Cuba between April 2009 and August 2010 - Amely Arencibia García; Alexander Piñon Ramos; Mayra Muné Jiménez; Belsy Acosta Herrera; Odalys Valdés Ramirez; Clara Savón Valdés; Susel Oropesa Fernandez; Grehete Gonzalez Muñoz; Yudira Soto Brito; Elias Guilarte García; Guelsys Gonzalez Baez; Bárbara Hernández; et al. (Journal of Infection in Developing Countries)
This item has no abstract. Follow the links below to access the full text.